2012
DOI: 10.1093/nar/gks554
|View full text |Cite
|
Sign up to set email alerts
|

PsRobot: a web-based plant small RNA meta-analysis toolbox

Abstract: Small RNAs (smRNAs) in plants, mainly microRNAs and small interfering RNAs, play important roles in both transcriptional and post-transcriptional gene regulation. The broad application of high-throughput sequencing technology has made routinely generation of bulk smRNA sequences in laboratories possible, thus has significantly increased the need for batch analysis tools. PsRobot is a web-based easy-to-use tool dedicated to the identification of smRNAs with stem-loop shaped precursors (such as microRNAs and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
345
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 440 publications
(347 citation statements)
references
References 45 publications
(62 reference statements)
2
345
0
Order By: Relevance
“…Similar to the initial computational prediction of miR5200a targets in wheat and barley (see Supplemental Figures 4A and 4B online), using psROBOT sRNA analysis toolbox (Wu et al, 2012), we identified two B. distachyon FT-like genes (Bradi2g07070 and Bradi1g48830), which were previously annotated as FTL1 and FTL2 (Higgins et al, 2010), as miR5200a targets (Figure 1C;see Supplemental Figures 4C and 4D online). Further validation through 59 RNA ligase-mediated RACE showed that both FTL1 and FTL2 mRNAs could be cleaved at miR5200 target sites in vivo, suggesting that these two FTs are bona fide miR5200 target genes ( Figure 1C).…”
Section: Mir5200 Targets Ft Orthologous Genes and Accumulates In Leavessupporting
confidence: 55%
“…Similar to the initial computational prediction of miR5200a targets in wheat and barley (see Supplemental Figures 4A and 4B online), using psROBOT sRNA analysis toolbox (Wu et al, 2012), we identified two B. distachyon FT-like genes (Bradi2g07070 and Bradi1g48830), which were previously annotated as FTL1 and FTL2 (Higgins et al, 2010), as miR5200a targets (Figure 1C;see Supplemental Figures 4C and 4D online). Further validation through 59 RNA ligase-mediated RACE showed that both FTL1 and FTL2 mRNAs could be cleaved at miR5200 target sites in vivo, suggesting that these two FTs are bona fide miR5200 target genes ( Figure 1C).…”
Section: Mir5200 Targets Ft Orthologous Genes and Accumulates In Leavessupporting
confidence: 55%
“…All primers are shown in Supplemental Table S4. Target genes of miRNAs in N. benthamiana were predicted by psRobot (Wu et al, 2012).…”
Section: Transient Agroinfiltration Assay In Nicotiana Benthamianamentioning
confidence: 99%
“…Target predictions were performed using psRobot_tar in psRobot [32] and through alignment with the U. pumila transcriptome (SRA database, SRP080724). The following criteria were then used to identify potential miRNA targets: (1) no more than four mismatches between the mature miRNA and its potential target site; (2) no more than one mismatch at nucleotide positions 1-9; (3) no more than two consecutive mismatches; and (4) no mismatches at positions 10 and 11 [30,33,34].…”
Section: Prediction Of Mirna Target Genesmentioning
confidence: 99%